The Relationship Between Bacterial Pattern with Degree of Airflow Limitation FEV1 in Acute Exacerbation of COPD at Adam Malik General Hospital and Pirngadi Hospital - Rianti Tarigan; Amira P Tarigan; Dian Dwi Wahyuni; Putri C Eyanoer (Jurnal Respirologi Indonesia, 2019)
Background: Respiratory tract infections are the leading cause of acute exacerbation of COPD (AECOPD). The aim of this study was to investigate the relationship between bacterial pattern and the degree of airflow limitation (FEV1) in patients with acute exacerbation of COPD at Adam Malik General Hospital and Pirngadi Hospital, also the sensitive antibiotics according to the susceptibility test. Methods: This was a cross sectional study of all patients admitted to Adam Malik and Pirngadi Hospital with AECOPD from September 2015 until September 2016. In all 45 subjects who fulfilled the inclusion criteria, the spirometry was examination undergone to evaluate the degree of severity of COPD according to GOLD 2017. In each sample sputum expectoration, the gram smear was made. Barttlet criteria was used to calculate the amount of epithelial cells and PMN. The sample was then grown on blood agar medium. Bacterial susceptibility test to antibiotics was conducted using VITEC 2 methods. Results: From 45 patients, 30 patients (66,7%) had positive sputum cultures. The most frequently isolated pathogen was Streptococcus pneumonia (26,7%). The most sensitive antibiotic was Amikacin (100%). There were no correlation between the in degree of airflow limitation FEV1 and bacterial sputum culture result. There were no significant differences between gram positive or negative bacteria with the degree of airflow limitation. Conclusion: The incidence of bacterial infection based on positive sputum culture in AECOPD was about 66,7% Streptococcus pneumonia was the most common pathogen and Amikacin was the most sensitive antibiotic. There were no significant correlation between the degree of airflow limitation FEV1 with the positive or negative sputum culture and also with the result of gram staining. (J Respir Indo. 2019; 39(3):204-9)